PENGARUH HARGA CPO (CRUDE PALM OIL), PERTUMBUHAN PENJUALAN, DAN SENSITIVITAS KURS TERHADAP RETURN SAHAM DI MASA PANDEMI COVID-19 (STUDI PADA SUBSEKTOR PERKEBUNAN KELAPA SAWIT YANG LISTING DI BURSA EFEK INDONESIA TAHUN 2020-2021) - Putri Widya; Rokhmawati Andewi; Fitri Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of CPO price, sales growth and exchangerate sensitivity on stock return in pandemic covid-19 era. The population in thisstudy palm oil plantation subsector companies listed on the Indonesia StockExchange (IDX) 2020-2021 period as many as 21 companies. The samplingtechnique used was purposive sampling method with the number of samples thatmet the criteria as many as 16 companies. This study used the Statistical Programfor Social Science (SPSS) as a method to analyze the data that has been obtained.The results showed that: (1) CPO price had a significant positive effect on stockreturn, (2) sales growth had a significant positive effect on stock return, (3)exchange rate had a positive and not significant effect on stock return, (4)simultaneously, CPO price, sales growth, and exchange rate had a significanteffect on stock return. Keywords: CPO Price, Sales Growth, Exchange Rate, Stock Return